EXAMINING THE EFFECTS OF RESEARCH AND DEVELOPMENT TAX DEDUCTIONS ON ADVANCED TECHNOLOGY FIRMS: AN INVESTIGATION INTO LEPU MEDICAL - Morrison, James A. (International Journal of Contemporary Research in Marketing and Management Sciences, 2024)
In the pursuit of high-quality economic development, innovation stands as a critical driver for enterprise adaptability and competitive advantage in a constantly changing macroenvironment. Despite its pivotal role, innovation is riddled with uncertainties and high sunk costs, which can deter enterprises from fully embracing it. Furthermore, the imperfect innovation protection system often results in free-riding financial subjects imitating and copying innovative products, diverting economic benefits away from the innovators. To address these challenges and foster innovation, governments have introduced tax incentives and other policies to regulate and promote enterprise innovation by effectively allocating resources in the market. Among these policies, research and development (R&D) expense deduction has emerged as a significant tool. The R&D expense deduction policy was first introduced in 2008 and has undergone several adjustments. The most recent changes, implemented in 2018, extended benefits to almost all enterprises, with certain exceptions, and increased the deduction percentage to 75%. Furthermore, the deduction for manufacturing enterprises was raised to a full 100% in 2021. These interventions aim to encourage enterprises to invest more in research and development activities, fostering a more innovative business landscape